Community Adaptation to Flood Disaster Risk in Koto Parik Gadang Diateh District, Solok Selatan Regency - Tri Perrapaula Tama; Paus Iskarni (Science and Environmental Journal for Postgraduate, 2019)
The purpose of this research was to know how the community of Koto Parik Gadang Diateh District in Solok Selatan adapted to the flood disaster risk. It was a descriptive qualitative research using purposive sampling technique to select the sample and interview and documentation to collect the data. The obtained data was then analized descriptively to present the facts found in the field. Types of community adaptation in the district were 1) Community passive and active adaptation to the flood disaster risk covered the activities of increasing income, elevating household appliances and equipment, and priotizing basic needs. 2) Community social adaptation to the flood disaster risk included well established kinship and sociological systems when the disaster hit and mutual cooperation to cope with the disaster. 3) Community economic adaptation to the flood disaster risk Included the community activities in fulfilling their clothing, food, and housing needs and donation from social organization such as the district officials, BPBD of Slok Selatan Regency (a regional disaster management agency), MRI (Indonesian Volunteer Community), ACT (Aksi Cepat Tanggap) and others. (4) Community cultural adaptation to the flood disaster risk. It related to the community customs, such as tahlilan and istighosa when they were having the misfortune and it also included constructing Floodway to reduce the flood risk. These 4 community adaptations interracted with each other and they were very important in facing flood risks. Keywords: Adaptation, Risk, Flood Disaster